The Surprising Incidence of a Tax on Pure Rent: A New Answer to an Old Question - Feldstein, Martin (Journal of Political Economy, 1977)
[The classic example of an unshiftable tax is the general tax on pure rental income. Since Ricardo, economists have believed that the annual net rental income of unimproved land falls by the amount of the annual tax and its price by the capitalized value of this tax. This paper shows that these conclusions are false, that the tax on pure land rents is at least partly shifted, and that the price of land may be increased by the imposition of a tax. Implications are suggested for the analysis of the corporate income tax and the taxation of natural resources.]